A CROSS-SECTIONAL STUDY TO EVALUATE CORRELATION BETWEEN NCV OF RIGHT UPPER LIMB AND LEFT UPPER LIMB IN A TERTIARY HEALTH CARE CENTRE OF WEST BENGAL - Dr. Washim Bari Rahaman, Dr. Tamal Chakraborty,Dr. Krishnendu Saha, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Nerve conduction velocity (NCV) is a vital neurophysiological parameter usedin the diagnosis and monitoring of peripheral nerve function. While inter-limb symmetry inNCV is generally assumed in healthy individuals, subtle differences may exist due to factorssuch as handedness, age, sex, and body composition. The present study aims to evaluate